Integration of Knowledge in Social Studies Subject at Bina Insan Elementary School - Jamilatul Husna; Salminawati Salminawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The conducted research took place at SD IT Bina Insan with the aim of investigating the implementation of integrated teaching activities between religious and general knowledge at the school. SD IT Bina Insan was chosen as the research subject because its program integrates religious knowledge with general subjects, aligning with the intended research focus. Moreover, such a learning program, emphasizing the integration of religious knowledge with general subjects, is relatively rare in other schools. The research utilized a qualitative method, and data collection was carried out through three stages, namely interviews, observations, and documentation. The results of the research revealed that the integration of religious knowledge with general subjects had been successfully implemented at SD IT Bina Insan, both in lower and upper grades. This study specifically focuses on observing the teaching and learning activities, particularly in the subject of Social Studies for Grade V, where the life stories of figures who fought against the Dutch colonial rule were connected with Hadiths from the Bukhari and Muslim collections, emphasizing the importance of fulfilling one's duties to the best of their abilities. The integration of religious knowledge with general subjects primarily occurred during the introduction phase, aiming to nurture generations and leaders who excel academically while upholding noble character traits.